Methodology Of Didactic Skills Development In Future Teachers - Yulduz Khudoyberdiyeva; Ikromjon Tursunov (Euro Asian Journal Publishing, 2024)
The article provides opinions, information and suggestions about organizational, communicative and didactic competencies necessary for independent education of students in pedagogical higher educational institutions, in particular, about improving didactic competencies. The information necessary for students' use of interactive methods in independent education is described.
Keywords: interactive; didactic; competence; communicative